2020
DOI: 10.1038/s41598-020-58457-x
|View full text |Cite
|
Sign up to set email alerts
|

AATF and SMARCA2 are associated with thyroid volume in Hashimoto’s thyroiditis patients

Abstract: Thyroid volume of Hashimoto's thyroiditis (HT) patients varies in size over the course of disease and it may reflect changes in biological function of thyroid gland. Patients with subclinical hypothyroidism predominantly have increased thyroid volume whereas patients with more pronounced hypothyroidism have smaller thyroid volumes. Suggested mechanism for thyroid atrophy is thyrocyte death due to apoptosis. We performed the first genome-wide association study (GWAS) of thyroid volume in two groups of HT patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…In addition, Pax-8, which was associated with the GO term 'nephron tubule formation' , participates in the pathogenetic process of AITD by regulating TG and TPO gene expression (26). SMARCA2, which is associated with vascular smooth muscle cell differentiation, is involved in apoptosis and thyroid volume in HT patients (27). Moreover, 34 signaling pathways associated with dysregulated miRNAs were identified by KEGG analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Pax-8, which was associated with the GO term 'nephron tubule formation' , participates in the pathogenetic process of AITD by regulating TG and TPO gene expression (26). SMARCA2, which is associated with vascular smooth muscle cell differentiation, is involved in apoptosis and thyroid volume in HT patients (27). Moreover, 34 signaling pathways associated with dysregulated miRNAs were identified by KEGG analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects: This is a retrospective observational study in which we used stored serum samples for vitamin D measurements, and phenotype information from HT patients and control participants from the CROHT biobank [ 34 , 35 ]. Total 25(OH)D (vitamin D in the text) was measured in 461 HT patients (92.41% females) and 176 control participants (93.75% females) by the LIAISON 25(OH) Vitamin D Total chemiluminescence immunoassay (DiaSorin, Saluggia, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…Given the inconclusive results on the relationship between vitamin D and HT, we aimed to perform a comprehensive set of analyses, in a large group of clinically diagnosed HT patients and control individuals from the Croatian Biobank of HT patients (CROHT biobank) [ 34 , 35 ] to give more conclusive results on this topic. A recent systematic review of vitamin D concentrations in relation to HT [ 29 ] pointed to several moderators that contribute to patient heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…A new publication on genetics has shown that the apoptosis antagonizing transcription factor (AATF) [92] is involved in thyroid disease in determining the volume of the gland in situations of thyroiditis [93] . AATF appears to regulate the anti-apoptotic effect of the unfolded protein response through transcriptional regulation of AKT1 [94] .…”
Section: An Interlude: Updating the Contribution Of Geneticsmentioning
confidence: 99%
“…These findings coincide with our previous description of the psychosomatic aspects of thyroid disease, where we found an association between magnesium deficiency and symptoms [194] . In 2020, Luka Brčić together with Ana Barić and others reported that the expression of AATF is diminished in cases of Hashimoto's thyroiditis and is associated with increased thyroid volume [93] . In the historical and experimental sections of this paper, we mentioned that increased thyroid volume has been a characteristic known for decades.…”
Section: A Concept Of Shared Resources As a General Basis Of Health Amentioning
confidence: 99%